Pengendalian Colletotrichum spp. Terbawa Benih Cabai dengan Paparan Gelombang Mikro - Lilih Naelun Najah; Mohamad Rahmad Suhartanto; Widodo Widodo (Jurnal Fitopatologi Indonesia, 2016)
Seed treatment using microwave has been reported as an effective and efficient method to control seed borne pathogens of chili pepper.  The purpose of this research was to evaluate the effectiveness of microwave irradiation treatment to suppress seedborne Colletotrichum spp. while maintaining physiological quality of chili’s seed.  First experiment was aimed to select the best condition for seed germination, and was done in completely randomized design with three levels of water content (4.31%, 6.33%, and 8.25%).  The second experiment was aimed to determine the best condition for disease suppression, and was done in completely randomized design with different levels of microwave irradiation duration (0, 10, 20, 30, 40, and 50 seconds) using the best seed water content level from the first experiment.  Application of systemic fungicide with benomyl as active ingredient (0.5 g L-1) was done as check treatment.  Four major species of Colletotrichum was found from chili’s seed, i.e. C. acutatum, C. capsici, C. gloeosporioides, and Colletotrichum sp. with C. acutatum as the predominant species.  The best water content level for microwave treatment was 4.31%. The most effective treatment was microwave irradiation duration for 40 seconds with efficacy rate of 64.5% for controlling seedborne C. acutatum on chili pepper.